2018
DOI: 10.1016/j.ajo.2018.04.010
|View full text |Cite|
|
Sign up to set email alerts
|

Vision Outcomes Following Anti–Vascular Endothelial Growth Factor Treatment of Diabetic Macular Edema in Clinical Practice

Abstract: DME patients receiving anti-VEGF therapy in clinical practice undergo less frequent monitoring and intravitreal injections, and achieve inferior vision outcomes to patients in landmark clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 27 publications
4
72
3
1
Order By: Relevance
“…It has been shown that patients generally received less injections than that given in clinical trials for n-AMD [30,31], DMO and RVOs [31][32][33]. This limits the effectiveness of anti-VEGF therapy in retinal vascular diseases [30][31][32][33][34][35][36].…”
Section: Limitations Of Anti-vegf Agents In the Treatment Of Retinal mentioning
confidence: 99%
“…It has been shown that patients generally received less injections than that given in clinical trials for n-AMD [30,31], DMO and RVOs [31][32][33]. This limits the effectiveness of anti-VEGF therapy in retinal vascular diseases [30][31][32][33][34][35][36].…”
Section: Limitations Of Anti-vegf Agents In the Treatment Of Retinal mentioning
confidence: 99%
“…Several real-life studies have been published for ranibizumab in DME treatment. 2,15,17,18,[29][30][31][32] A commonality of these studies is that the number of injections, functional outcomes, and structural outcomes are comparatively worse than in the pivotal RCTs. Even though our study reports values that are consistent with the real-life data previously published for DME patients undergoing anti-VEGF treatment, direct comparison is impossible.…”
Section: Comparing Our Results To Published Real-life Datamentioning
confidence: 99%
“…In addition, the number of injections was generally greater in patients in RCTs, who had greater letter gains compared with patients in real-world studies. An analysis of 1-year visual acuity outcomes from electronic medical records suggests that infrequent dosing might compromise the extent of vision improvement gained with anti-VEGF therapy during the first 12 months of treatment [18]. A comparison of DME trials shows that fixed dosing regimens [55] or strict PRN regimens with clear retreatment criteria [48] help to maximize the gains in BCVA, leading to optimal outcomes for patients.…”
Section: Discussionmentioning
confidence: 99%